Magnetic Molecular Rectangles Constructed from Functionalized Nitronyl‐Nitroxide Ligands and Lanthanide(III) Ions. Issue 6 (29th December 2020) - Calancea, Sergiu; Carrella, Luca; Mocanu, Teodora; Sadohin, Vladimir; Raduca, Mihai; Gutu, Iacob; da Rocha, Julio C.; Vaz, Maria G. F.; Rentschler, Eva; Andruh, Marius
Abstract: Five binuclear complexes with rectangular topology have been synthesized using a nitronyl‐nitroxide ligand (L) functionalized with a pyrazole coordinating group: [Ln2 (hfac)2 L2 ], with Ln=Eu (1 ), Gd (2 a, 2 b ), Tb (3 ), Dy (4 ), Tm (5 ). The Eu III and Tm III complexes crystallize in the P 21 / n space group, while the Gd III, Tb III, and Dy III derivatives crystalize in P ‐1 space group. The crystal structures for compounds 2 a, 3, 4, and 5 have been fully solved, while for compounds 1 and 2 b, the unit cell parameters have been measured and compared with crystals 3 and 5 . Crystals 2 a ( P 21 / n ) and 2 b ( P ‐1) are polymorphic forms. In these complexes the nitronyl‐nitroxide ligand bridges two metal ions through one aminoxyl group and the pyrazole fragment. In the five complexes the Ln III ions show a coordination number of eight with a triangular dodecahedron geometry. The magnetic properties of all five complexes have been investigated. For compounds 2, 3, and 4 the Ln III ‐Rad interaction was found to be ferromagnetic: J GdRad =2.09(1) cm −1 [ H =‐2 J GdRad ( S Gd1 S Rad1 + S Gd2 S Rad2 ], J TbRad =1.93(14) cm −1, J DyRad =1.72(14) cm −1 . The Tm III ‐Rad coupling is antiferromagnetic ( J TmRad =−0.53(1) cm −1 ). For the Tb III, Dy III, and Tm III complexes the effects of the crystal field have been taken into account in the fitting procedure. Abstract : A series of five binuclear 2 p ‐4 f complexes has been obtained using as a bridging ligand a new nitronyl‐nitroxide radical functionalized with a N ‐donor group. The magnetic properties of these rectangular‐shaped complexes have been investigated.